Adaptive data distribution technique for enhancing MB-OFDM UWB link performance in detect and avoid environments. (18th February 2011) - Rateb, Ahmad M.; Syed Yusof, S.K.; Fisal, Norsheila
Detect-and-avoid (DAA) mechanisms were developed to minimise potential interference caused by ultra wideband (UWB) systems to in-band active narrowband links. Interference is reduced by minimising emitted power in overlapping bands to create a spectral notch, which provides a certain level of isolation between both systems. Although it has been proved that this procedure deteriorates UWB link performance significantly, no research suggested any scheme to mitigate it. In this paper, we introduce the adaptive data distribution (ADD) technique, which we developed to enhance UWB link performance upon employment of DAA. ADD technique is confined to the physical layer and is fully transparent to the MAC sub-layer. Results have shown a significant reduction in error rates that could provide an SNR gain of at least 4 dB for most covered scenarios. In addition, ADD technique renders performance less sensitive to transmission mode variation and augments its coexistence capability by enabling a UWB device to safely notch 16-55% of its bandwidth.